1988
DOI: 10.1002/jcp.1041350108
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recombinant CSF‐1 on the blast cells of acute myeloblastic leukemia in suspension culture

Abstract: Recombinant hemopoietic colony-stimulating factors (CSFs), including GM-CSF, G-CSF and IL-3, have been shown to be effective stimulators of both self-renewal and terminal differentiation of blast stem cells in acute myeloblastic leukemia (AML). We have examined the activity of a fourth growth factor, recombinant CSF-1 (or M-CSF), on the growth of leukemic blasts in culture. CSF-1 was found to be active on some, but not all, blast populations. In sensitive cells, CSF-1 often stimulated the production of adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…[15][16][17][18][19][20][21] From these in vitro studies it has been suggested that these growth factors also may play an essential role in the in vivo proliferation of most AML cells.…”
Section: Figurementioning
confidence: 99%
“…[15][16][17][18][19][20][21] From these in vitro studies it has been suggested that these growth factors also may play an essential role in the in vivo proliferation of most AML cells.…”
Section: Figurementioning
confidence: 99%
“…6 More particularly, recombinant IL-3 and granulocyte macrophage-CSF (GM-CSF) induce leukemic colonies and activate DNA synthesis in more than 80% of AMLs. [7][8][9][10] No clear relationship between IL-3 and GM-CSF responses and the French-American-British (FAB) classification of acute leukemias was observed. 6 Furthermore, leukemic cells may produce one or more of the principal HGFs, including IL-3 and GM-CSF.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 AML samples are highly heterogeneous in their need for growth factors to support both clonogenic growth 50 and survival in suspension culture. 51 In some cases of AML, growth factors may be needed to maintain pathways that protect the mitochondrial membrane from depolarization. We therefore hypothesized that samples that undergo the most spontaneous apoptosis in vitro have mitochondrial membranes that depolarize the most readily.…”
Section: Mtp Sensitivity To Mclccp In Primary Aml Blasts and Cell Linesmentioning
confidence: 99%